2018
DOI: 10.1007/s13592-018-0562-6
|View full text |Cite
|
Sign up to set email alerts
|

Queen mandibular pheromone modulates hemolymph ecdysteroid titers in adult Apis mellifera workers

Abstract: -To test the hypothesis that exposure to queen mandibular pheromone (QMP) modulates ecdysteroid production in adult worker honey bees, ecdysteroids were measured in hemolymph and other tissues of individual adult worker honey bees reared with or without QMP in cages and field colonies. Ecdysteroid titers were higher in caged workers exposed to QMP continuously from the first day of adult life than in workers reared without QMP. Statistical cluster analysis suggested the possibility that a subgroup of workers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…This evolutionary history is reflected today by the partitioned expression of the same genome between workers and queens 29,119,120 . This plastic state is still observed in species considered to be "facultatively social" (note that this label does not imply that all social species progress along similar or predictable evolutionary paths 18 122 , control of nutritional intake 123 , and multiple modes of physical interaction such as piping and drumming 124 . In various ant and bee species, secretions passed among workers and queens can influence the fertility of all engaged actors, and thus influence colony productivity overall.…”
Section: Eusocial Colony Physiology: Hormonal Mechanisms and Evolutiomentioning
confidence: 99%
See 1 more Smart Citation
“…This evolutionary history is reflected today by the partitioned expression of the same genome between workers and queens 29,119,120 . This plastic state is still observed in species considered to be "facultatively social" (note that this label does not imply that all social species progress along similar or predictable evolutionary paths 18 122 , control of nutritional intake 123 , and multiple modes of physical interaction such as piping and drumming 124 . In various ant and bee species, secretions passed among workers and queens can influence the fertility of all engaged actors, and thus influence colony productivity overall.…”
Section: Eusocial Colony Physiology: Hormonal Mechanisms and Evolutiomentioning
confidence: 99%
“…Regulation of fertility in the eusocial insect colony occurs via a variety of mechanisms that are all essentially absent in solitary insects. These mechanisms include short-range chemical signaling 122 , control of nutritional intake 123 , and multiple modes of physical interaction such as piping and drumming 124 . In various ant and bee species, secretions passed among workers and queens can influence the fertility of all engaged actors, and thus influence colony productivity overall.…”
Section: Case Studies In Colony Physiology: Ancestral Traits Under Co...mentioning
confidence: 99%
“…In D. melanogaster , both fru (Dalton et al, 2009) and ERR (Kovalenko et al, 2019) have been shown to regulate similar genes known to be induced by ecdysone receptor (EcR) signalling. In honey bees, EcR knockdown is associated with differences in transcript levels of several genes discussed above, including Kr‐h1 (Mello et al, 2014), and QMP exposure is associated with high ecdysteroid titres (Trawinski & Fahrbach, 2018). In our study, fru was paternally biased in unresponsive workers, whereas ERR was maternally biased in responsive workers.…”
Section: Discussionmentioning
confidence: 99%
“…Cages also received the QMP treatment for the duration of those 3 or 8 days. Synthetic QMP ("TempQueen"; Betterbee Inc.) was presented as a slow-release strip placed at the bottom of the QMP+ cages, while QMP− cages did not receive a QMP strip, as in an earlier study [21]. The strip was used according to the manufacture instructions and contained an equivalent of the 5-component blend of QMP.…”
Section: Honey Beesmentioning
confidence: 99%